A comparative analysis of pain reduction following a single intra-articular injection of platelet-rich plasma, steroid or normal saline in chronic external shoulder impingement syndrome - Shete, Mohit R.; Popere, Sanjay V.; Khan, Rushan; Kulkarni, Abhay P.; John, James (International Journal of Research in Orthopaedics, 2023)
Background: Shoulder impingement is a common diagnosis for patients with pain and dysfunction of shoulder joint. Due to its chronicity of clinical manifestation of the impingement syndrome, there is a need to find new therapies that collaborate to improve pain management. Methods: A hospital based descriptive, epidemiological study was conducted with 150 patients. The patients were divided in the following three groups of 50 patients each: Platelet-rich plasma (PRP) group: 50 patients received PRP, steroid group: 50 patients received steroid injection normal saline group: 50 patients received normal saline injection. Baseline visual analogue scale (VAS) score on overhead activities were recorded. After the 4th week, 12th week, and 24th week, patients were examined in the outpatient clinic. The main outcome measure was pain with overhead activities using a VAS. Results: The VAS score improved significantly in PRP group and Steroid group compared to normal saline group at the 4th week, 12th-week and 24th-week follow-up periods post injection, as per ANOVA test (p<0.05). Conclusions: PRP and steroids, both can be considered effective methods to treat pain in chronic shoulder impingement syndrome (SIS) and less invasive compared to surgical treatment. They improve the pain and hence shoulder function in chronic impingement syndrome.